Managing Tinea Cruris During Pregnancy: Therapeutic Dilemmas and Clinical Considerations - Molla Andriska Dewi; Flora Marlita Lubis (GLOBAL HEALTH SCIENCE GROUP, 2025)
Tinea cruris (dermatophytic infection of the groin) is a common superficial fungal infection. Increased levels of estrogen and progesterone during pregnancy can affect the immune system and skin homeostasis, creating a favorable environment for the growth of dermatophyte fungi. Its management during pregnancy poses clinical challenges, as the choice of antifungal therapy must balance maternal symptom relief with fetal safety. We report the case of a 21 years old pregnant woman in her third trimester who presented with pruritic, erythematous plaques in the inguinal region, clinically diagnosed as tinea cruris. Laboratory confirmation was achieved through potassium hydroxide (KOH) microscopy and fungal culture with sabaround dextrose agar. Considering gestational safety, topical terbinafine therapy was initiated, and systemic antifungals were avoided. Supportive measures, including hygiene optimization and avoidance of occlusive clothing, were reinforced. Symptomatic relief and lesion resolution were achieved within four weeks without maternal or fetal complications. The case highlights the therapeutic dilemma of managing tinea cruris in pregnancy, where systemic antifungals are often contraindicated. Topical terbinafine remain the mainstay of treatment, with satisfactory efficacy and safety profiles. Clinicians must carefully individualize therapy, prioritizing non-teratogenic options while ensuring effective infection control to prevent recurrence. Topical antifungal therapy is the mainstay of treatment for tinea cruris in pregnancy due to safety concerns with systemic agents. This case demonstrates that terbinafine cream is effective and well tolerated, with complete resolution and no maternal or fetal complications.